2019
DOI: 10.1002/ecy.2665
|View full text |Cite
|
Sign up to set email alerts
|

Exotic plant species are locally adapted but not to high ultraviolet‐B radiation: a reciprocal multispecies experiment

Abstract: Ultraviolet (UV) radiation intensities differ among global regions, with significantly higher levels in the southern hemisphere. UV‐B may act as an environmental filter during plant invasions, which might particularly apply to plant species from Europe introduced to New Zealand. Just like for any other abiotic or biotic filter, successful invaders can cope with novel environmental conditions via plastic responses and/or through rapid adaptation by natural selection in the exotic range. We conducted a multispec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…In consequence, the applied UV-B intensity was familiar to the level exotic populations experience but novel to native individuals only. The observed limiting effects of UV-B radiation on leaf number, leaf length and rosette area confirm previous studies, which also reported UV-B-induced growth and biomass reduction [17,19,29,44]. A UV-B-induced increase in PSII efficiency was determined in the present study and caused by a decrease of minimum and maximum chlorophyll fluorescence (see also [45]).…”
Section: Single and Combined Effects Of Uv-b And Droughtsupporting
confidence: 92%
See 1 more Smart Citation
“…In consequence, the applied UV-B intensity was familiar to the level exotic populations experience but novel to native individuals only. The observed limiting effects of UV-B radiation on leaf number, leaf length and rosette area confirm previous studies, which also reported UV-B-induced growth and biomass reduction [17,19,29,44]. A UV-B-induced increase in PSII efficiency was determined in the present study and caused by a decrease of minimum and maximum chlorophyll fluorescence (see also [45]).…”
Section: Single and Combined Effects Of Uv-b And Droughtsupporting
confidence: 92%
“…Overall irradiation and biologically active UV-B radiation levels are equally subjected to climate change and are becoming more important for both resident plant communities and plant invasions [14]. However, these factors have been largely neglected in plant invasion research (see however: [15][16][17]). The effects of global change have largely been under consideration to date as 'one-factor-only' approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the mean UV‐B intensities in their native range, the higher was the LDMC ind under UV‐B radiation exposure. As LDMC is known for its ability to respond plastically and its protective effect against high‐energy radiation, one could expect a more pronounced response of preadapted species as observed in the experiment (Hock et al., 2019; Robson et al., 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Higher leaf number of plants in the New Zealand experiment either indicates a generally more productive environment in comparison to the German common garden (see Hock et al., 2019) or a functional response to different environmental conditions that could not be controlled for in the experiments. Such differences might be a result of several biotic and abiotic factors, most notably those related to higher temperature or more sunshine hours, but might also derive from altered biotic interactions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation